2015
DOI: 10.1371/journal.pone.0141743
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metabolic Profiles in Women are Menopause Dependent

Abstract: Menopause is an endocrinological transition that greatly affects health and disease susceptibility in middle-aged and elderly women. To gain new insights into the metabolic process of menopause, plasma metabolic profiles in 115 pre- and post-menopausal women were systematically analyzed by ultra-performance liquid chromatography/mass spectrometry in conjunction with univariate and multivariate statistical analysis. Metabolic signatures revealed considerable differences between pre- and post-menopausal women, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
3
21
1
Order By: Relevance
“…It has been reported before [ 1 , 19 ] and is in line with our own data that concentrations of some metabolites in women do not change continuously with age, but show a sudden increase or decrease in concentration around the age of 50 that is associated with menopause. For men, metabolite concentration changes with age occur continuously starting at 30 or 40 years of age ( S4 Fig ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It has been reported before [ 1 , 19 ] and is in line with our own data that concentrations of some metabolites in women do not change continuously with age, but show a sudden increase or decrease in concentration around the age of 50 that is associated with menopause. For men, metabolite concentration changes with age occur continuously starting at 30 or 40 years of age ( S4 Fig ).…”
Section: Discussionsupporting
confidence: 93%
“…Generally, as reported by others [ 1 , 7 , 18 , 19 , 42 , 50 , 60 ], we found that several amino acids, lipids, and organic acids in plasma are important for the prediction of age in women, with ornithine, choline, hippuric acid, cholesterol, glucuronic acid, and glucose occurring in metabolite patterns for chronological age and menopause ( S3 Table ). Interestingly, all these metabolites have higher concentrations in older and post-menopausal women, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In our study, we also identified metabolites of these classes; however, the species of LPC and LPE differed from those that we identified as changed in post-menopausal women, possibly due to the lipid extraction methods (acetonitrile x MeOH / CHCl3) [2], the technology used in the detection (UPLC-QTOF/MS x FIA-ESI-MS/MS), as well as the biological sources of the population studied.…”
Section: Discussionmentioning
confidence: 73%